2021
DOI: 10.21037/qims-21-203
|View full text |Cite
|
Sign up to set email alerts
|

Can virtual touch tissue imaging quantification be a reliable method to detect anterior talofibular ligament type I injury at the acute, subacute, and chronic stages?

Abstract: Background: Anterior talofibular ligament (ATFL) injury affects ankle joint stability. To date, very few studies have examined tissue stiffness changes inside injured ligaments. Virtual touch tissue imaging quantification (VTIQ) allows for the non-invasive quantitative measurement of tissue stiffness. The present study aimed to examine the efficacy of VTIQ as a method for detecting ligament injury.Methods: A total of 206 patients diagnosed with unilateral ATFL type I injury (81 acute cases, 69 subacute cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The ratio of the apparent elastic modulus obtained from elastography to that measured from the conventional mechanical test varies in different tissues and perhaps increases with the increase of soft tissue stiffness. Previous literature about elastography assessment of ATFL have reported SWV values ranging between 1.79 m/s ( Hotfiel et al, 2018 ) and 7.6 m/s ( Chen et al, 2021 ) for the healthy controls. The mean SWV value of ATFL in the control group in this study was within the variation range of the literature data mentioned before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of the apparent elastic modulus obtained from elastography to that measured from the conventional mechanical test varies in different tissues and perhaps increases with the increase of soft tissue stiffness. Previous literature about elastography assessment of ATFL have reported SWV values ranging between 1.79 m/s ( Hotfiel et al, 2018 ) and 7.6 m/s ( Chen et al, 2021 ) for the healthy controls. The mean SWV value of ATFL in the control group in this study was within the variation range of the literature data mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study about re-sprains during the 12 months of follow-up after an initial ankle sprain suggested that up to 55% of individuals sustained instability, and 28% of the participants reported at least one re-sprain (van Middelkoop et al, 2012). Previous studies have observed ATFL thickness differences in ligament injury, which can be detected using ultrasound in B-mode and MRI but without clear diagnosis criteria of ligament thickness (Kanamoto et al, 2014;Chen et al, 2021). The diagnostic criterion for the acute posterior cruciate ligament injury was larger than 6.5 mm (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive virtual touch tissue imaging quantification, a novel ultrasonic palpation method, can identify the hardness difference of acute type I ATFL injuries and evaluate ligament elasticity. These are all new methods for quantifying ankle ligament stiffness and diagnosing and monitoring ATFL injury[ 31 ]. According to the examination results, physicians can time the treatment plan appropriately, develop a more effective rehabilitation plan, further improve the outcomes, promote ATFL injury healing, accelerate ankle joint function recovery, and reduce the occurrence of complications.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…At present, ultrasonic techniques that can quantitatively measure tissue hardness include virtual touch tissue imaging (VTIQ) and SWE. They both are non-invasive technologies that can quantitatively evaluate the elasticity of the mass by measuring average shear wave velocity (SWV) of a region of interest (ROI) in the mass ( 10 , 11 ). SWE can convert SWV into Young’s modulus, and the stiffness of the mass is expressed in Kpa.…”
Section: Introductionmentioning
confidence: 99%